The Partisipasi Perangkat Daerah Pemerintah Provinsi Jambi Dalam Upaya Meningkatkan Ekosistem Inovasi (Tantangan Dan Peluang) - LESTARI, WENI; Martin, Joni (Jurnal Khazanah Intelektual, 2025)
This study aims to describe the existing state of regional innovation in Jambi Province and the partisipation of regional government agencies in improving the Regional Competitiveness Index (IDSD) and the Regional Innovation Index (IID). Data were obtained from government documents and related academic research. The results indicate that the IDSD and IID scores are gradually recovering. The participation by regional agencies has fluctuated, indicating human resources capacity issues in proposing innovations. Recommendations are include maintaining institutional consistency, encouraging cross-regional collaboration, and ensuring that each OPD is required to produce at least one innovation per year to maintain regional compretitiveness. Keywords: Competitiveness, Innovation, Regional Govetnment Agencies.